An experimental interaction platform for local music scene in Malaysia/ Alya Abu Bakar ... [et al.] - Abu Bakar, Alya; Mohd Shuib, Ahmad Sofiyuddin; Mohd Pahme, Nur Faizah; Soedewi, Sri (Universiti Teknologi MARA, Perak, 2024)
There have always been problems on the local music scene, which isn't surprising when you consider that our country lacks the education and culture to support live music, particularly independent live music. It is imperative that the government increase its support for the independent music industry. The proposal does not even have support from the public. Instead of working together and providing support for one another, too many micro communities are cut up and focused on competition. The local music scene is going through a difficult time now because there are not enough platforms and venues that allow bands and artists to showcase their work. To find a solution to the problem, this research is being carried out to develop a mobile application as an interaction platform for the local music scene. With this app, the Malaysian local music scene would be able to learn about new events and event organizers would have an easier time promoting their own activities. During this investigation, both qualitative and quantitative approaches are utilized to collect data from the local bands and artists in Malaysia, as well as from the UI/UX designer. The findings of this study could be very significant in terms of making the local music scene and up-and-coming artists more accessible to the public in the form of an application since it is both contemporary and convenient.